Politik Kewargaan: Melacak Perjuangan Kelompok Penghayat Kerohanian di Kota Malang dalam Mendapatkan Hak sebagai Warga Negara - Qisthi, Ainun (Universitas Brawijaya, 2023)
This research aims to explain how spiritual groups in Malang City struggle to obtain their rights as citizens. This research is important to carry out as a benchmark for the obligations that the government should give in the form of rights as citizens to marginalized groups, in this case spiritual believers in Malang City, Malang City. By borrowing the theoretical framework of citizenship politics from Kristian Stokke, which divides citizenship into four dimensions, namely citizenship as legal status, citizenship as rights, citizenship as membership, and citizenship as participation. This research uses descriptive qualitative methods by collecting data through literature study, document study, interviews and observation. The results of this research show that spiritual groups in Malang City have made various efforts as a form of struggle to obtain various rights, namely membership rights, legal status as an organization or community, civil rights, social rights, political rights and participation rights. The findings of this study show that groups of religious believers in Malang City have proven to be very proactive and take initiative towards government institutions in various fields such as administration, education and the social sphere.